2018
DOI: 10.1108/ijhcqa-11-2016-0179
|View full text |Cite
|
Sign up to set email alerts
|

Structural quality of healthcare facilities in India

Abstract: Purpose Although India has a number of health issues, the healthcare facilities in India are insufficient due to poor quality of care. The purpose of this paper is to examine the factors affecting the structural quality of healthcare facilities in India. Design/methodology/approach This study used the medical facility data from the India Human Development Survey-II, 2011-2012 (ICPSR 36151) ( n=4,218). Logistic regression was conducted to predict structural quality of healthcare facilities. Findings The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…There are some empirical studies which have identified causes for low access to healthcare and poor quality of healthcare services in Uttar Pradesh. It was found that poor quality of care is one of the reasons for insufficient healthcare facilities (Prinja, et al, 2012) and poor structural quality of hospitals and healthcare centres in the state (Armentha, et al, 2018). Narang (2010) used an adopted scale for measuring quality of healthcare services in Uttar Pradesh and found that availability of both medical equipment and doctors for women were negatively associated with the quality of healthcare facilities in the state.…”
Section: Review Of Literaturementioning
confidence: 99%
“…There are some empirical studies which have identified causes for low access to healthcare and poor quality of healthcare services in Uttar Pradesh. It was found that poor quality of care is one of the reasons for insufficient healthcare facilities (Prinja, et al, 2012) and poor structural quality of hospitals and healthcare centres in the state (Armentha, et al, 2018). Narang (2010) used an adopted scale for measuring quality of healthcare services in Uttar Pradesh and found that availability of both medical equipment and doctors for women were negatively associated with the quality of healthcare facilities in the state.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A tool was developed, taking into consideration the quality parameters of healthcare settings in the Indian context, and with reference to the available literature (Kwan et al, 2019;Aggarwal et al, 2019;Armenta et al, 2018;Panda and Kondasani, 2017;Kanwar et al, 2016). While developing the tool, the authors also referred to survey manuals regarded as the common standards on quality and safety management in Besides, 30 binary response items (Yes/No) were incorporated into the questionnaire to measure the employees' perception of the processes and outcomes of their respective hospitals.…”
Section: Instrumentmentioning
confidence: 99%
“…The World Health Organization, 1946, affirmed that “the highest attainable standard of health is a fundamental right of every human being” (Nicholson et al, 2016 ). Understanding health as a fundamental human right formulates a legal obligation on the respective governments to provide their citizens with accessible, available, and affordable quality healthcare (Armenta et al, 2018 ). The Study by Youkta et al ( 2022 ) reveals that out-of-pocket expenditure by households in India accounts for 60.6% of total health expenditures and 2.3% of the country’s GDP, indicating poor misallocation of funds.…”
Section: Introductionmentioning
confidence: 99%